ESENSI PLURALISME NOVEL RUMAH DI SERIBU OMBAK KARYA ERWIN ARNADA ANALISIS SOSIOLOGI SASTRA - Yeskris, Yater Atrida (Humanis, 2014)
This thesis the essence of pluralism of the novel Rumah di Seribu Ombak. Analysis of the sociology literature in the novel divided into four aspects. There are social (society) aspect, education aspect, religion aspect, and morals aspect. The results of analysis social (society) aspect are about the tolerance respected people in Kalidukuh village although they are of different religions. The results of a education aspect are about the figures formal, informal, and non-formal education. The results of religion aspect are about two religions, Islam dan Hinduism are adopted of the figures in the novel. The results of morals aspect are about attitude towards people of different religions to be able to appreciate each other. Rumah di Seribu Ombak novel is a small portrait of the beauty of the difference when people can uphold religious tolerance attitude.
Keywords: Pluralism, Sociology of Literature, Rumah di Seribu Ombak Novel